A bibliometric and visualization analysis for global research trends in Wushu and mental health (1981–2024) - Liu, Shu Chen; Cheah, Kenny S. L.; Syed Ali, Syed Kamaruzaman Bin; Qu, Hui Min; Wang, Zhen Lin (Frontiers in Psychiatry, 2026)
BackgroundMental health has become one of the most urgent public health issues in the 21st century, and the COVID-19 pandemic has significantly increased this problem. As a traditional mind-body practice, Wushu (e.g., Tai Chi, Qigong) is increasingly recognized for its therapeutic potential in mental health. However, bibliometric studies in this eld remain scarce.MethodsThis study aims to visualize the Wushu and mental health (WMH) related research through bibliometric analysis of the Web of Science database (1981–2024). It examines publication trends, core journals, international collaboration, leading authors, and thematic evolution. A systematic search using Boolean operators identified 536 articles. To conduct a complementary analysis of the findings, this study compared the 23 clinical trials identified from PubMed (2020–2024) with the research trends obtained from the bibliometric analysis.ResultsThe study found that the number of published articles and cited times increased significantly in the past five years, which confirmed the influence of COVID-19 in this field. China and the United States, represented by Harvard University, are the main pushing forces in this area. The research focus has shifted from rehabilitation orientation to comprehensive mental and public health perspectives. Future development trends may include strengthening international cooperation, standardizing intervention programs, and cross-cultural research.ConclusionThis multi-database analysis provides researchers and policymakers with a scientific reference for the WMH field. It clearly reflects current research trends and future research directions in WMH.